2012
DOI: 10.1016/j.cmet.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

DEPTOR Cell-Autonomously Promotes Adipogenesis, and Its Expression Is Associated with Obesity

Abstract: DEP domain containing mTOR-interacting protein (DEPTOR) inhibits the mechanistic target of rapamycin (mTOR) but its in vivo functions are unknown. Previous work indicates that Deptor is part of the Fob3a quantitative trait locus (QTL) linked to obesity/leanness in mice with Deptor expression being elevated in white adipose tissue (WAT) of obese animals. This relation is unexpected considering the positive role of mTOR in adipogenesis. Here, we dissected the Fob3a QTL and show that Deptor is the highest priorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
153
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(170 citation statements)
references
References 43 publications
14
153
1
2
Order By: Relevance
“…A recent study showed that POMC-specific ablation of p70 S6 kinase 1 (S6K1), a downstream substrate of mTORC1, affects hepatic glucose production and peripheral lipid metabolism without affecting energy balance (35). It was reported that reducing S6K1 activity, an effect observed in response to DEPTOR overexpression (6,19,31), increases hepatic glucose output (35). Supporting these results, we observed that hepatic glucose production was significantly increased in POMC-Deptor O/E mice.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A recent study showed that POMC-specific ablation of p70 S6 kinase 1 (S6K1), a downstream substrate of mTORC1, affects hepatic glucose production and peripheral lipid metabolism without affecting energy balance (35). It was reported that reducing S6K1 activity, an effect observed in response to DEPTOR overexpression (6,19,31), increases hepatic glucose output (35). Supporting these results, we observed that hepatic glucose production was significantly increased in POMC-Deptor O/E mice.…”
Section: Discussionsupporting
confidence: 77%
“…Further investigations are needed to determine whether the inhibition of S6K1 in POMC neurons plays an important role in mediating the effect of DEPTOR on liver metabolism. Over the years, it was shown several times that DEPTOR promotes insulin signaling by dampening the feedback inhibition from mTORC1 to phosphoinositide-3-kinase (PI3K), which leads to an activation of protein kinase B (Akt/PKB) (6,19,22,23,31). Defining whether changes in insulin signaling contribute to modulate the brain-liver connection that we report here represents another key question that will require additional experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Laplante et al recently reported that overexpression of the mTOR inhibitor DEPTOR promotes adipogenesis in vivo ( 42 ), which corroborates our main conclusion in this study. Overexpression of DEPTOR is found to suppress Ser636/639 phosphorylation of IRS1 and enhance Akt phosphorylation in adipocytes ( 42 ).…”
Section: Downloaded Fromsupporting
confidence: 82%
“…Overexpression of DEPTOR is found to suppress Ser636/639 phosphorylation of IRS1 and enhance Akt phosphorylation in adipocytes ( 42 ). DEPTOR is capable of inhibiting both mTORC1 and mTORC2 kinase activity ( 43 ); hence, the differential effects of DEPTOR overexpression on mTORC1 inhibition of Akt and mTORC2 activation of Akt mirror those of mTOR depletion.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Whether LMO3 and Dexras1 interface in regulating adipogenesis is unclear. DEPTOR, a component of the mTOR system (25), may also interface with the Dexras1 system, because DEPTOR is induced by glucocorticoids and promotes adipogenesis (26). Our findings may be relevant to clinical instances of glucocorticoid-associated adiposity.…”
Section: Discussionmentioning
confidence: 79%